O espetáculo está no ar! Moda, consumo e mídia no Noroeste do Paraná - Martins, Carla Cristina Siqueira (2014)
The Tailoring activity stands out in the Brazilian state of Paraná, mainly in the Northwest and North of it, in cities like Londrina, Apucarana, Maringá and Cianorte, that form the so-called 'Corridor of fashion' and represent 35% of establishments in textile-clothing industry of the state. (PREFEITURA DE CIANORTE, 2013). Knowing the representativity of such industry, this dissertation aims to understand how fashion is conceived and experienced by women with different profiles in the city of Cianorte. The main objective is to analyze fashion as social phenomenon, and the specific objectives are to discuss the relationship between consumption of fashion, media and spectacle society, and interpret what is the relationship women residents in this city have with fashion sector. For that, theoretical discussion was held, having as guidance the authors Diane Crane (2006), Gilles Lipovestky (1989, 2005, 2007 , 2009 , 2011), Jean Baudrillard (1996, 2008), Daniel Miller (2007, 2013) and Guy Debord (1997); and field research, in which were interviews in Cianorte thirteen women, using the techniques of semi structured interview, open interviews, focus groups and life history.The research revealed the strong influence of media culture in everyday life, consumption practices and fashion conceptions of such women, mainly in relation to television media, in special soap opera. It brought to the surface features of an increasingly global society, where resources and media stimuli are used in the spectacularization of the individual and in his quest for social notoriety.